REPRESENTATION OF NATURE IN THE ART OF “BELATIK” AND ITS IMPLICATIONS FOR LITERATURE LEARNING - Fikri, Muhammad Zakiul; Ernalida (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study aims to explore the meaning of pantun in the “belatik” art of the Jerieng community in Bangka and connect it with the concept of ecocriticism. The focus is to identify representations of ecological concepts, including pollution, wilderness, apocalypse, dwellings, animals, and the earth. The research employed a qualitative approach with ecocritical analysis of data in the form of belatik lyrics, collected through observation and note-taking from live performances, as well as in-depth interviews with belatik artists. The findings reveal that belatik represent five main ecological concepts: pollution, willderness, dwellings, animals, and the earth. These representations are conveyed through natural symbols, references to local flora and fauna, and depictions of the interconnectedness between humans and the environment. The art of belatik serves not only as a form of cultural expression but also as a medium for delivering ecological messages rich in local wisdom. This research underscores the potential of traditional arts as a medium for literary education capable of fostering ecological awareness in society.